2015
DOI: 10.1016/j.rboe.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Length of preoperative hospital stay: a risk factor for reducing surgical infection in femoral fracture cases

Abstract: ObjectiveTo analyze infections of the surgical site among patients undergoing clean-wound surgery for correction of femoral fractures.MethodsThis was a historical cohort study developed in a large-sized hospital in Belo Horizonte. Data covering the period from July 2007 to July 2009 were gathered from the records in electronic medical files, relating to the characteristics of the patients, surgical procedures and surgical infections. The risk factors for infection were identified by means of statistical tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
1
16
0
4
Order By: Relevance
“…In our study, we also found a preoperative hospital stay for at least 4 days to be an independent predictor for POI. A presurgical hospital stay of more than 4 days has been reported to be associated with higher risk of POI in inpatients recovering from trauma (OR 1.58, 95% CI 1.1–2.35) as well as in orthopedic patients (OR 3.3, 95% CI 2.5–4.0) . While appropriate to minimize surgical delay in hospitalized IBD patients, this may not be clinically feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we also found a preoperative hospital stay for at least 4 days to be an independent predictor for POI. A presurgical hospital stay of more than 4 days has been reported to be associated with higher risk of POI in inpatients recovering from trauma (OR 1.58, 95% CI 1.1–2.35) as well as in orthopedic patients (OR 3.3, 95% CI 2.5–4.0) . While appropriate to minimize surgical delay in hospitalized IBD patients, this may not be clinically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…A presurgical hospital stay of more than 4 days has been reported to be associated with higher risk of POI in inpatients recovering from trauma (OR 1.58, 95% CI 1.1-2.35) 25 as well as in orthopedic patients (OR 3.3, 95% CI 2.5-4.0). 26,27 While appropriate to minimize surgical delay in hospitalized IBD patients, this may not be clinically feasible. Although other risk factors including history of POI, history of COPD, and RBC transfusion within 6 months are not modifiable, surgeons may consider patients with these risk factors at a higher risk of POI.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Pereira and associates, it was established that the patients who had pre-operatively stayed in hospital longer than 4 days acquired SSIs three times more frequently (OR=3.3) ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Postsurgical complications (PSCs) are defined as a deviation from the normal postsurgical course and can be divided into minor and major complications or graded by severity and treatment requirements [2]. A large number of risk factors are related to PSCs including type and extent of the surgical procedure, perioperative bleeding, anesthetic method, patient's age, condition and nutritional state [3][4][5][6][7][8][9]. By recent statistics, there are nearly 234 million major surgical procedures are conducted all around the world each year comprises the rates of major PSCs ranging from 3% to 16% [10].…”
Section: Introductionmentioning
confidence: 99%